Investigation of the lipid profile in patients with subclinical hypothyroidism - musavi, hadis; Abbasi, Mojtaba (Archives of Medical Laboratory Sciences, 2019)
Background: Hypothyroidism is a thyroid gland-related disorder which causes lipid metabolism disturbance. Subclinical Hypothyroidism (SCH) is a compensatory stage in the course of this disease, in which TSH production increases while the levels of thyroid hormones are in normal or low-normal range. There are no studies about the lipid profile abnormalities in SCH. Therefore, the aim of this study was to evaluate the lipid profile in SCH patients and compare it with normal individuals. Methods: In this case-control study, subjects were randomly chosen among 800 individuals referred to Neka city hospital in Mazandaran province, Iran in order to routine biochemical and thyroid hormone checkup. Participants were divided into two groups ; cases (n=400) and controls (n=400). Thyroid hormones were measured by ELISA, and lipid profile parameters were evaluated colorimetrically by AutoAnalyzer. Results: There were no significant differences in age and sex distribution between the two groups. Among the measured thyroid hormones, TSH was significantly different between the two groups (p≤ 0.05). In case of lipid profile, high-density lipoprotein cholesterol (HDL-C) was significantly different between the two groups (p≤ 0.05). However, no significant differences were observed in the amount of low-density lipoprotein cholesterol (LDL-C), triglyceride (TG) and cholesterol (p>0.05). Conclusion: SCH patients, showed a decrease in HDL-C. It can be concluded that subclinical hypothyroidism similar to hypothyroidism can cause lipid metabolism disturbance.